High- Risk Factors Associated with Inferior Alveolar Nerve Injury Following Removal of the Third Molars: A Preliminary Study - Pelin Güneri; Hayal Boyacıoğlu; Meltem Özden Yüce; Betül Karaca; Nezaket Ezgi Özer (Ankara University, 2023)
PURPOSE: This study aims to determine the incidence of inferior alveolar nerve (IAN) injury following the extraction of the lower third molars (LTMs) and to identify the demographic, radiographic, and intra-operative risk factors associated with this complication. MATERIALS amp; METHODS: Fifty LTMs from 47 patients were included in this prospective clinical study. Demographic data and intra-operative parameters including operation time, bone removal and duration, excessive bleeding and IAN exposure were recorded. Bone retention, anatomical position of LTMs (Pell amp;Gregory and Winter classification) and 5 radiographic criteria proposed by Rood and Shehab were evaluated on panoramic images, whereas the distance between roots and the inferior alveolar canal (IAC), the cortication status of IAC, and the buccolingual position of IAC were examined on CBCT images. Chi-square test was used to compare the presence of IAN injury with variables. A p-value lt; 0.05 was considered as statistically significant. RESULTS: The incidence of temporary IAN injury was 6% among study population. No permanent IAN injury was observed. Excessive bleeding (p=0.007), IAN exposure (p=0.007), the lingual position of IAC (p=0.035) and dumbbell-shaped IAC (p=0.002) were found to be associated with increased risk of temporary IAN injury. CONCLUSION: Identification of high-risk factors is essential for predicting the risk of IAN injury, and determining the most convenient treatment plan for each case. Further studies with larger study samples are needed both to confirm the risk factors that are proposed in the present study and to identify the other potential ones.